Biotransformation of cyclohexane and related alicyclic hydrocarbons by Candida maltosa and Trichosporon species. (February 2016) - Dallinger, Anja; Duldhardt, Ilka; Kabisch, Jan; Schlüter, Rabea; Schauer, Frieder
Abstract: The hydrocarbons of crude oil and oil products such as gasoline or diesel oil comprise an aliphatic, an aromatic, and an alicyclic fraction. The alicyclic fraction represents a group of substances which, along with polycyclic hydrocarbons and tar-like components, are among the most biodegradation resistant components of oil. The major part of the alicyclic oil fraction is made up of cyclohexane and its derivatives. Little is currently known about the microbial, especially fungal, degradation of alicyclic hydrocarbons. In this study, the ability of yeasts of the genera Candida and Trichosporon to use cyclohexane and some related alicyclic hydrocarbons as substrates was investigated. The anamorphic ascomycetous yeast Candida maltosa and different strains of the anamorphic basidiomycetous yeast genus Trichosporon are not able to utilize cyclohexane as carbon source when present at 0.005%–1.0% and at concentrations of over about 0.5% cyclohexane is toxic for them. However at concentrations of 0.25%–0.4% the yeasts can oxidize cyclohexane and transform it via cyclohexanol to cyclohexanone. Cyclohexanone seems to be a dead-end-product for these yeasts because no further conversion of cyclohexanone to ε-caprolactone could be demonstrated. Analysis of the cycloalkane oxidation after cell cultivation with different carbon sources revealed that non-specific enzymes were involved and no additional enzyme induction seems to occur in the presence of cycloalkanes. Highlights: First report about the biotransformation of alicyclic hydrocarbons by yeasts. Cycloalkanes are transformed by alkane-utilizing and non-alkane-utilizing yeasts. Cyclohexane is transformed to cyclohexanol and cyclohexanone by the yeasts. The transformation is independent of the growth substrate. Cyclohexane is no growth substrate and toxic in concentrations higher than 0.5%.